(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
This article discusses the uses of the term motivation in the psychological field, presenting, briefly and superficially, historical origins of human motivation research and a few epistemological problems related to conceptualization of motives. This article also presents a brief overview of the variety of definitions of motivation, found in psychological books and manuals. Also discussed are the concepts of science, psychology, and the issue about human motives hierarchies, emphasizing the need to recognize interaction processes as relevant in the study of motivation: (1) how certain behaviors, under certain conditions, invariably occur after certain environmental changes; (2) how certain environmental changes, under certain conditions, are followed by certain behaviors, not others that would be possible; (3) how certain behaviors occur cyclic, even in the absence of environmental changes, (4) how certain behaviors, under certain conditions, occur even in the absence of environmental changes; and (5) how certain environmental changes happen to be part of organism-environment interactions, while others don’t.